2016
DOI: 10.1093/cid/ciw578
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-effectiveness Analysis of Preexposure Prophylaxis for the Prevention of HIV Among Los Angeles County Men Who Have Sex With Men

Abstract: PrEP and test-and-treat offer cost-effective alternatives to the status quo. The success of these strategies depends on ART and PrEP adherence and initiation rates. The lack of evidence on adherence behaviors toward PrEP, therefore, warrants further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 26 publications
2
45
1
1
Order By: Relevance
“…We searched PubMed from 1 January 2013 to 11 October 2017 with the terms "HIV" AND ("PrEP" OR "PrEP") AND ("cost" OR "costeffectiveness") with the goal of identifying any new studies that have appeared since the 2013 meta-analysis of PrEP cost-effectiveness modelling studies [32]. The search retrieved 149 abstracts, of which 21 provided country-specific estimates of the cost-effectiveness of various PrEP implementation strategies [6,8,9,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. This study is not only the first to provide data and evidence on the costs and cost-effectiveness of providing oral PrEP to MSM in Thailand, but is also the first such study from the Asia-Pacific region.…”
Section: Discussionmentioning
confidence: 99%
“…We searched PubMed from 1 January 2013 to 11 October 2017 with the terms "HIV" AND ("PrEP" OR "PrEP") AND ("cost" OR "costeffectiveness") with the goal of identifying any new studies that have appeared since the 2013 meta-analysis of PrEP cost-effectiveness modelling studies [32]. The search retrieved 149 abstracts, of which 21 provided country-specific estimates of the cost-effectiveness of various PrEP implementation strategies [6,8,9,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. This study is not only the first to provide data and evidence on the costs and cost-effectiveness of providing oral PrEP to MSM in Thailand, but is also the first such study from the Asia-Pacific region.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently shown that PrEP is cost-effective in populations with highly concentrated HIV epidemics. A study comparing various strategies to curb HIV transmission among MSM living in San Francisco found PrEP to be cost effective at a cost of $27,863–$37,181 quality-adjusted life years (QALY) gained (U.S. threshold $150,000) (Drabo, Hay, Vardavas, Wagner, & Sood, 2016). These findings are consistent with a study in New York City, which found that PrEP among high risk MSM would cost $32,000/QALY (Desai et al, 2008).…”
Section: Addressing Barriers To Prep Uptakementioning
confidence: 99%
“…Substantial gaps remain in understanding the trade-offs between the costs and benefits of choosing alternative HIV prevention strategies, such as the initiation of PrEP by high risk uninfected individuals [13]. Mathematical models of HIV that include PrEP are scarce [6].…”
mentioning
confidence: 99%